1996
DOI: 10.1088/0022-3727/29/2/010
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of micrometre and sub-micrometre particles by high-frequency electric fields and hydrodynamic forces

Abstract: We demonstrate that micrometre and sub-micrometre particles can be trapped, aggregated and concentrated in planar quadrupole electrode configurations by positive and negative dielectrophoresis. For particles less than in diameter, concentration is driven by thermal gradients, hydrodynamic effects and sedimentation forces. Liquid streaming is induced by the AC field itself via local heating and results, under special conditions, in vortices which improve the trapping efficiency. Microstructures were fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
127
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 17 publications
8
127
0
2
Order By: Relevance
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to those previously studied in eDEP [34][35][36][37][38][39][40][41][42][43][44][45][46][47], electrothermal flows in iDEP devices also arise from the action of the electric field (both DC and AC) on fluid inhomogeneities (predominantly electrical properties including conductivity and permittivity) formed in the constriction region due to Joule heating-induced temperature gradients. Figure 4 shows the numerically predicted temperature and electric field contours in the constriction region at 100 V DC/500 V AC.…”
Section: Resultssupporting
confidence: 63%
“…It has been long known in capillary electrophoresis that Joule heating can elevate the buffer temperature and disturb the electroosmotic flow causing significant sample dispersion [30][31][32][33]. The effects of Joule heating on fluid temperature and motion in eDEP have been investigated previously [34][35][36][37][38]. It was reported that a pair of counter-rotating fluid circulations could form near the microelectrodes [39].…”
Section: Introductionmentioning
confidence: 99%
“…The mean free path of the movement is inversely dependent on mass, implying that decreases in the particle diameter require significant increases in the applied electrostatic energy (or field strength). The stable trapping of viruses and beads has been demonstrated previously [6][7][8][9]. Here we show that nanometre sized latex spheres can be both stably trapped in nanofabricated electrode arrays and, more importantly, that a heterogeneous mixture can be separated into two populations using dielectrophoresis.…”
supporting
confidence: 70%
“…Dielectrophoretic forces have been used to separate and manipulate cells, 2,11 bacteria, 12,13 viruses, 14 and submicron latex spheres. 5,15,16 Recently the dielectrophoretic manipulation of DNA molecules has led to applications such as the concentration of DNA molecules, [17][18][19] DNA-protein interaction studies, 20,21 and molecular surgery of DNA. 22 However, a detailed understanding of the behavior of surface-immobilized DNA molecules when exposed to high frequency ac electric fields, and in particular the orientation and elongation of DNA as a result of dielectrophoretic force and torque, has not yet been established.…”
Section: Introductionmentioning
confidence: 99%